Using digital repositories to support project based word in on-line education - Castrillón Ojeda, Carolina; Meza Vega, Erwin (Revista Colombiana de Computación, 2007)
In order to take full advantage of the resources offered by content repositories, it is essential to combine the use of these resources witch some teaching/learning strategies or methodologies, such as project based work. Keywords: project Based Work, Digital Repositories, Sharable Content Objects, Virtual Learning Environmenst.